2020
DOI: 10.18502/ijph.v48i6.2924
|View full text |Cite
|
Sign up to set email alerts
|

Out of Pocket Payment and Affordability of Medication for Geriatric Patients in Tehran, Iran

Abstract: Background: Considering the importance of high out-of-pocket (OOP) payment (OOPP), as a marker of health system performance, and affordability of medications in the elderly, this study was conducted to determine these issues. Methods: In this cross-sectional study, prescriptions of patients aged 65 yr or older from 5 university-affiliated pharmacies in Tehran, Iran were evaluated from Jan to Mar 2014. Prescriptions were selected from four insurance organizations. We used the prescriptions data regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
0
18
0
2
Order By: Relevance
“…This retrospective cross sectional study, conducted from January to March 2014, was part of a project that evaluated different aspects of pharmacotherapy for outpatient geriatrics (18,19). Data of 1512 insurance prescriptions of patients aged ≥ 65 years were collected from 5 pharmacies (Amini, Booali, Isar, Taleghani and Abedini) affiliated to the Faculty of Pharmacy, Tehran University of Medical Sciences (TUMS).…”
Section: Methodsmentioning
confidence: 99%
“…This retrospective cross sectional study, conducted from January to March 2014, was part of a project that evaluated different aspects of pharmacotherapy for outpatient geriatrics (18,19). Data of 1512 insurance prescriptions of patients aged ≥ 65 years were collected from 5 pharmacies (Amini, Booali, Isar, Taleghani and Abedini) affiliated to the Faculty of Pharmacy, Tehran University of Medical Sciences (TUMS).…”
Section: Methodsmentioning
confidence: 99%
“…High OOP is a marker of health system performance. 19 Previous research has shown that OOP is prevalent among insured populations, especially in low and middle-income countries; for instance, in the population with health insurance in Indonesia, 18% of patients experienced catastrophic medical costs. 20 This was also true in the population of India with National Health Insurance in that 66.0% of the beneficiaries incurred OOP.…”
Section: Introductionmentioning
confidence: 99%
“…Price of medicines is a concern in low- and middle-income countries where up to 90% of the population purchases medicines through out-of-pocket payments [ 14 ]. This has a huge impact on the affordability of medicines and treatment outcome of diseases [ 15 ].…”
Section: Introductionmentioning
confidence: 99%